2020
DOI: 10.3389/fphys.2020.01059
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of Bone Morphogenetic Protein 7 in Shell Formation and Growth in the Razor Clam Sinonovacula constricta

Abstract: Bone morphogenetic proteins (BMPs) not only play essential roles in bone development but also are involved in embryonic growth, organogenesis cell proliferation and differentiation. However, the previous studies on the functions of shellfish BMPs genes are still very limited. To better understand its molecular structure and biological function, BMP7 of the razor clam Sinonovacula constricta ( Sc-BMP 7) was cloned and characterized in this study. The full length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…It has been proposed that SNP, a molecular genetic marker of the third generation, has a good application prospect in population genetic analysis of aquatic animal, molecular marker–assisted selection (MAS) and biological evolution ( Wenne, 2017 ). Increasing evidence has shown that some SNPs are associated with growth, disease resistance, and other economic traits of clams ( He et al, 2012 ; Siva et al, 2012 , 2016 ; Nie et al, 2015 ; Niu et al, 2015 ; Yao et al, 2020 ; Zhao et al, 2020 ). For instance, a synonymous mutation SNP c.852A > G of insulin-like growth factor 2 mRNA-binding protein gene in Patinopecten yessoensis showed a significant association with the growth traits ( Ning et al, 2018 ), while two SNPs HbIIA-E2-146 and HbIIB-E2-23 of the hemoglobin gene ( Hb ) in Tegillarca granosa were associated with the Vibrio parahaemolyticus resistance ( Bao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that SNP, a molecular genetic marker of the third generation, has a good application prospect in population genetic analysis of aquatic animal, molecular marker–assisted selection (MAS) and biological evolution ( Wenne, 2017 ). Increasing evidence has shown that some SNPs are associated with growth, disease resistance, and other economic traits of clams ( He et al, 2012 ; Siva et al, 2012 , 2016 ; Nie et al, 2015 ; Niu et al, 2015 ; Yao et al, 2020 ; Zhao et al, 2020 ). For instance, a synonymous mutation SNP c.852A > G of insulin-like growth factor 2 mRNA-binding protein gene in Patinopecten yessoensis showed a significant association with the growth traits ( Ning et al, 2018 ), while two SNPs HbIIA-E2-146 and HbIIB-E2-23 of the hemoglobin gene ( Hb ) in Tegillarca granosa were associated with the Vibrio parahaemolyticus resistance ( Bao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dsRNA of PfN23 gene was injected into the adult pearl oyster (Pinctada fucata), resulting in a disordered of nacre surface, suggesting that PfN23 gene may be a key accelerator in the control of crystal growth in nacre (Fang et al, 2012). Similarly, the expression of the BMP7 gene was successfully suppressed by injecting dsRNA into the razor clam, indicating that the BMP7 gene plays a vital role in repairing shell damage (Zhao et al, 2020). Moreover, in our previous study, the silencing of Glutamate dehydrogenase, a gene related to ammonia nitrogen detoxification, was induced by the injection of specific siRNA into the razor clam (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β superfamily includes TGF-βs, growth differentiation factors (GDFs), bone morphogenetic proteins (BMPs), Inhibins/Activins, and Nodal. All members of the TGF-β superfamily release mature polypeptides by division of precursors at specific sites, and the activity relies on the formation of dimers from the same or different subunits [ 6 , 7 ]. Although the TGF-β family contains many diverse factors, they all signal via conserved signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between Smads and other signaling proteins mediates regulatory signals, controlling the expression of target genes, the translation of mRNA translation, and the regulation of cytoplasmic protein [ 8 , 9 , 10 , 11 ]. In recent years, the TGF-β superfamily has been found to play a critical role in the growth and development of shellfish [ 7 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation